Construction Process Climate Impacts under Denmark’s 2025 Building Regulations - Falbe-Hansen, David Bro (My University, 2025)
This thesis investigates climate impacts from construction processes (modules A4 and A5) under Denmark’s 2025 Building Regulations and in accordance to EN 15978 using a detailed case study of a 14,000 m2 residential development in a Copenhagen suburb. The thesis assesses reported climate impacts using the regulatory methodology and explores how both physical project parameters and methodological variation influence outcomes. The baseline assessment shows that total A4 and A5 impacts exceed the regulatory threshold by 15 percent with construction waste alone accounting for 80 percent of total emissions. This dominance is not attributed to excessive waste generation but to the regulatory assessment method which applies the highest impact factor to entire mixed waste fractions. Scenario-based sensitivity analyses reveal that while changes in geographic sourcing and material substitution have limited effects, methodological differences such as assessment approach and an updated waste assessment method can alter reported impacts by up to 1.4 kg CO2e/m2year equivalent to 94 percent of the regulatory threshold without altering physical parameters. These findings highlight a misalignment between the threshold setting dataset and the regulatory assessment method raising concerns about the method’s accuracy in assessing actual climate performance. The thesis recommends that the method applied to construction waste and the calibration of threshold values be reconsidered to better reflect real world conditions. For practitioners it identifies practical strategies for increasing the accuracy of reported impacts and reducing both reported and actual emissions through procurement choices and improved waste handling on site.
Keywords: construction process, LCA, mitigation, regulatory compliance, scenario analysis, transport, construction waste, carbon, sensitivity, buildings.